2010
DOI: 10.1364/oe.18.003660
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization with orbital angular momentum beams

Abstract: Intense laser ionization expands Einstein's photoelectric effect rules giving a wealth of phenomena widely studied over the last decades. In all cases, so far, photons were assumed to carry one unit of angular momentum. However it is now clear that photons can possess extra angular momentum, the orbital angular momentum (OAM), related to their spatial profile. We show a complete description of photoionization by OAM photons, including new selection rules involving more than one unit of angular momentum. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…These light beams, which carry orbital angular momentum (OAM) [17] that can be transferred to atoms, molecules, and nanostructures [18][19][20][21][22][23], have already been utilized at visible and infrared wavelengths in a wide variety of applications, ranging from micromanipulation [24], detection of spinning objects [25], microscopy [26], and optical data transmission [27][28][29]. Perhaps the most promising applications of vortex beams at short wavelengths are in x-ray magnetic circular dichroism, where different OAM states allow the separation of quadrupolar and dipolar transitions [30], photoionization experiments, where the dipolar selection rules are violated giving rise to new phenomena beyond the standard effect [31], and in resonant inelastic x-ray scattering, where vortex-beam-mediated coupling to vibrational degrees of freedom could provide important information on a wide range of molecular materials [32].In the case of visible light, OAM is commonly generated by sending the beam through a suitable optical element (e.g., a spiral phase plate). This technique has been used in the past to produce XUV or x-ray beams that carry OAM [33,34].…”
mentioning
confidence: 99%
“…These light beams, which carry orbital angular momentum (OAM) [17] that can be transferred to atoms, molecules, and nanostructures [18][19][20][21][22][23], have already been utilized at visible and infrared wavelengths in a wide variety of applications, ranging from micromanipulation [24], detection of spinning objects [25], microscopy [26], and optical data transmission [27][28][29]. Perhaps the most promising applications of vortex beams at short wavelengths are in x-ray magnetic circular dichroism, where different OAM states allow the separation of quadrupolar and dipolar transitions [30], photoionization experiments, where the dipolar selection rules are violated giving rise to new phenomena beyond the standard effect [31], and in resonant inelastic x-ray scattering, where vortex-beam-mediated coupling to vibrational degrees of freedom could provide important information on a wide range of molecular materials [32].In the case of visible light, OAM is commonly generated by sending the beam through a suitable optical element (e.g., a spiral phase plate). This technique has been used in the past to produce XUV or x-ray beams that carry OAM [33,34].…”
mentioning
confidence: 99%
“…For example, absorption and photoionization of atoms, molecules, and nanostructures with vortex beams offer a richer light-matter interaction beyond the customary plane-wave selection rules [79][80][81][82][83][84][85][86][87][88][89]. Those open new prospects for spectroscopy in the XUV and X-ray regime, such as exciting forbidden-electric-dipole transitions in quantum dots [90], discerning the magnetic sublevels in atoms and clusters [91], inducing charge current loops in fullerenes controlled by the topological charge of the vortex [92], novel dichroism absorption spectroscopy beyond circularly polarized light [93][94][95], and for the production of unconventional skyrmionic defects [96], which are very promising to produce magnetic memory devices at the nanometer scale [97].…”
Section: Perspectives and Applicationsmentioning
confidence: 99%
“…Let us consider a left circularly polarized LG beam (σ = +1 in Eqs. (6)(7)(8)) with l = +2 is interacting with a BEC of 10 3 number of 23 Na atoms in an anisotropic harmonic trap. The axis of the beam and the axis of the trap are same and along z axis of the laboratory frame.…”
Section: Quadrupole Interaction Of a Bec With An Lg Beam: Numerimentioning
confidence: 99%
“…Many researchers have predicted that the field OAM can be transferred to the internal motion of an atom [4][5][6][7][8] or a molecule [9][10][11] in electronic dipole or quadrupole transitions, while some works [12,13] have shown that the field OAM does not interact with molecular chirality. Applications have been proposed based on direct coupling of field OAM to the internal motion [4,7,8,11,[14][15][16][17] or to the c.m. motion only [18][19][20].…”
Section: Introductionmentioning
confidence: 99%